2020
DOI: 10.1039/d0ew00397b
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics removal in wastewater treatment plants: a critical review

Abstract: Wastewater treatment plants (WWTPs) are an important route for microplastics to enter aquatic environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(167 citation statements)
references
References 73 publications
4
121
1
1
Order By: Relevance
“…It is not within the remit of this review to discuss the many different processes involved in the treatment of wastewaters around the world, or, equally, the ways in which wastes are transferred into the treatment plants. Certainly, however, WWTP effluents represent a critical path for microplastics to enter aquatic ecosystems (Magni et al, 2019;Iyare et al, 2020) and so their inclusion in this review is necessary. Iyare et al (2020), in a review of removal of microplastics from WWTPs, stated that average removal rates over 21 studies were 72% during preliminary and primary treatment steps, while secondary and tertiary WWTPs raised this figure to 88% and 94%, respectively.…”
Section: Wastewater Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not within the remit of this review to discuss the many different processes involved in the treatment of wastewaters around the world, or, equally, the ways in which wastes are transferred into the treatment plants. Certainly, however, WWTP effluents represent a critical path for microplastics to enter aquatic ecosystems (Magni et al, 2019;Iyare et al, 2020) and so their inclusion in this review is necessary. Iyare et al (2020), in a review of removal of microplastics from WWTPs, stated that average removal rates over 21 studies were 72% during preliminary and primary treatment steps, while secondary and tertiary WWTPs raised this figure to 88% and 94%, respectively.…”
Section: Wastewater Systemsmentioning
confidence: 99%
“…Certainly, however, WWTP effluents represent a critical path for microplastics to enter aquatic ecosystems (Magni et al, 2019;Iyare et al, 2020) and so their inclusion in this review is necessary. Iyare et al (2020), in a review of removal of microplastics from WWTPs, stated that average removal rates over 21 studies were 72% during preliminary and primary treatment steps, while secondary and tertiary WWTPs raised this figure to 88% and 94%, respectively. However, the majority of the studies focussed on plastic microbeads, and not fibres.…”
Section: Wastewater Systemsmentioning
confidence: 99%
“…P.U. Iyare et al [5] showed that the bulk of the removal of MPs, at an average of 72%, comes during pre-and primary treatment. Dris et al reported 69% MP retention in the pre-and primary stages of a WWTP in Paris [98].…”
Section: Retention Of Mps In Preliminary and Primary Treatment Stages Of Wwtpsmentioning
confidence: 99%
“…A number of reviews have appeared on the topic of wastewater treatment and microplastic retainment [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Over the last 10 years, the understanding of microplastics and their impact on the environment has developed as have the analytical techniques to identify and quantify microplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MPs removal through a tertiary treatment process as a final treatment by application of membrane technology has received increased attention due to its versatility, and higher MPs removal potential (Lu et al 2016;Salerno et al 2016;Lares et al 2018). Previous studies have shown that membrane treatment presents a higher MPs removal efficiency (.99%) in comparison with the preliminary, primary, and secondary treatment processes (Sun et al 2019;Iyare et al 2020). However, the robust performance of the membrane process depends on the wastewater, physicochemical futures of MPs, as well as the membrane applied (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%